Collapse mechanism and shaking table test validation of a 3D mid-rise CFS composite shear wall building. (January 2020) - Jiang, Liqiang; Ye, Jihong
Abstract: Structural vulnerability theory (SVT) is a method that identifying the weakness and potential collapse modes of building structures in the finite element (FE) aspect, and the determinant of the global stiffness matrix |K |≤0 is proposed as the judgment of collapse of building structures. Due to the limitation of the SVT in identifying plastic hinge failure modes of the framed structures, this paper proposes the improved SVT (SVT), in which the transformation processes of the connections from rigid ones to pinned ones are considered. Based on the foundations of the ISVT using in planar framed structures, which was conducted by the authors, this paper develops the ISVT from 2-dimension to 3-dimension, and a 5-story cold-formed steel (CFS) building was tested to verify the ISVT. The results show that: the predicted collapse mode with maximum vulnerability index from the ISVT is same with the failure patterns of the test building, the first unzipped elements predicted by the ISVT are same with the most serious damaged components observed form the test. Such two aspects demonstrate the feasibility of the ISVT in revealing the collapse mechanism of the 3D CFS structures. Besides, this paper recommends the expected collapse mode for mid-rise CFS structures, and proposes "strong-frame weak-wall" concept to realize seismic design of the expected collapse mode. The findings can be used for collapse resistance design for mid-rise CFS buildings subjected to earthquakes. Highlights: Collapse mechanism of CFS structures was analyzed theoretically. An improved structural vulnerability theory (ISVT) is proposed for collapse analysis of CFS structures. Possible collapse modes of CFS structures were identified by clustering and unzipping processes. A 5-story CFS building was tested by the authors to validate the theoretical results. An expected collapse mode was recommended for the mid-rise CFS structures.